The Historical Meaning of the Presumption of Innocence - Shehu, Lola (European Journal of Multidisciplinary Studies, 2018)
The presumption of innocence is one of the fundamental and most important principles of the due legal process. No principle of criminal and procedural law has ever caused more interest and debate than the rule that every person is presumed innocent until his guilt is proved by a court decision. The presumption of innocence is a legal right of any person in the modern state of law who is suspected of committing a criminal offense. It is the principle that gave life and historical rivalry between the civil law and the common law, which is reflected in the application of the principle of guilt in the typical continental right and the application of the principle of the presumption of innocence to the common law system. Despite this somewhat artificial distinction that happens from time to time, the role of this principle can not be denied even in civil law. The presumption of innocence is closely related to the other essential principles of the criminal procedure such as the right to protection or the right of the suspect to have available the necessary procedural means to present his case without being disadvantaged with the other party. The contradictory, together with the guarantee for an independent and impartial tribunal serve as elements to safeguard the principle of presumption of innocence at least in the context of narrowly procedural aspects.